Perkembangan Ekonomi Islam Di Indonesia Melalui Penyelenggaraan Fintech Syariah - Fauzi, Muhammad Ibnu Faruk (AL-BAYAN: JURNAL HUKUM DAN EKONOMI ISLAM, 2024)
As a country with the largest Muslim population in the world, Indonesia has great potential to be able to develop its economy through an Islamic economy, one of which is through the implementation of Financial technology (fintech), which is an innovation in financial services using technology so that people can easily access financial products and services that are not available. can be accommodated by traditional financial services. This research is a type of library research. The focus of library research is to find various theories, laws, propositions, principles, or ideas that are used to analyze and solve formulated research questions. The nature of this research is descriptive analysis. The development of Islamic economic law is basically parallel to other conventional economic laws. The existence of Islamic economics in general in Indonesian society is conceptually in accordance with the demands of the times. The Islamic finance industry in Indonesia has been recognized and implemented by the public. The legal umbrella of Sharia Fintech itself is also based on Financial Services Authority Regulation (POJK) 77 of 2016 and sharia fintech also refers to the Fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN MUI) Number 117/2018 regarding Information Technology-Based Financing Services Based on Sharia Principles.